2015
DOI: 10.3233/jad-150453
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Factors Associated with the Cognitive and Emotional Efficacy of Regular Musical Activities in Dementia

Abstract: Recent evidence suggests that music-based interventions can be beneficial in maintaining cognitive, emotional, and social functioning in persons with dementia (PWDs). Our aim was to determine how clinical, demographic, and musical background factors influence the cognitive and emotional efficacy of caregiver-implemented musical activities in PWDs. In a randomized controlled trial, 89 PWD-caregiver dyads received a 10-week music coaching intervention involving either singing or music listening or standard care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 39 publications
3
46
1
1
Order By: Relevance
“…Särkämö et al (2008Särkämö et al ( , 2010Särkämö et al ( , 2014a. Särkämö et al (2014bSärkämö et al ( , 2016a.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Särkämö et al (2008Särkämö et al ( , 2010Särkämö et al ( , 2014a. Särkämö et al (2014bSärkämö et al ( , 2016a.…”
Section: Discussionunclassified
“…The emotional and well-being effects of singing in dementia have thus far been explored in two RCTs and in one non-randomised study. In our own three-arm RCT (see above), the singing intervention (familiar songs sung in a group and in a PWD-caregiver dyadic setting at home) was found to be effective short-term in reducing depression ( Figure 5A), especially the physical signs of depression (e.g, lack of energy), as well as long-term in reducing caregiver stress and burden ( Figure 5B) (Särkämö et al, 2014(Särkämö et al, , 2016a. In a smaller non-RCT study on mild-moderate PWDs (N = 20), Satoh et al (2015) also observed that a 6-month karaoke-based singing training reduced neuropsychiatric symptoms and improved sleep time compared to a control group.…”
Section: Expressive Music Interventions In Dementia Carementioning
confidence: 99%
“…A recent review of six randomized controlled studies found beneficial effects with respect to depression and anxiety symptoms [52]. Music therapy has also been shown to have some benefits with regard to reducing neuropsychiatric symptoms [53,54], improving symptoms of anxiety and depression [55,56], enhancing cognitive performance and quality of life [55,57], and even for improving or stabilizing certain aspects of self-awareness [58]. Other studies have found that cognitive stimulation therapy can improve cognition [59,60] and quality of life [59,61], reducing apathy and symptoms of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Community group singing is growing in popularity as an activity to support the mental wellbeing of people with dementia and their carers. There is evidence from neuropsychology that singing provides cognitive stimulation through multiple effects on the brain, but that response to singing is mediated by clinical and demographic factors [5]. A randomised trial compared the effects of singing, listening to music and usual care for person with dementia/carer dyads, and found that both singing and listening to music improved mood, orientation and remote episodic memory, whilst singing also improved carer wellbeing [6].…”
Section: Background and Rationalementioning
confidence: 99%